2007
DOI: 10.3390/s7040473
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of a Flexible Strain Sensor for Textile Structures Based on a Conductive Polymer Composite

Abstract: Abstract:The aim of this work is to develop a smart flexible sensor adapted to textile structures, able to measure their strain deformations. The sensors are "smart" because of their capacity to adapt to the specific mechanical properties of textile structures that are lightweight, highly flexible, stretchable, elastic, etc. Because of these properties, textile structures are continuously in movement and easily deformed, even under very low stresses. It is therefore important that the integration of a sensor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
224
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 329 publications
(229 citation statements)
references
References 31 publications
4
224
0
1
Order By: Relevance
“…2,[12][13][14] Such remarkable advances have been achieved through various solutions through the use of electrical active matrices on flexible rubberlike substrates to obtain various functions, such as high bendability, 15,16 ultrasensitivity, 7,17 transparency, 1,2,18-21 or wellestablished human-device interfaces. 8,9,22,23 In general, to be able to measure multifunctional mechanical and electrical signals, a number of circuit elements involving organic/inorganic matrix arrays, 3,4,17,[24][25][26][27][28][29][30][31] hybrid composites, [32][33][34][35][36][37][38] graphene, 39,40 and nanowires (NWs) or nanotube assemblies [41][42][43][44] need to be integrated on various flexible substrates. 45 About a decade ago, flexible electronic skins (e-skins) for pressure sensing were first introduced with polymer-based switching matrices for future displays, robots, and prosthetics of mechanical communications [ Figure 1(a)].…”
Section: Introductionmentioning
confidence: 99%
“…2,[12][13][14] Such remarkable advances have been achieved through various solutions through the use of electrical active matrices on flexible rubberlike substrates to obtain various functions, such as high bendability, 15,16 ultrasensitivity, 7,17 transparency, 1,2,18-21 or wellestablished human-device interfaces. 8,9,22,23 In general, to be able to measure multifunctional mechanical and electrical signals, a number of circuit elements involving organic/inorganic matrix arrays, 3,4,17,[24][25][26][27][28][29][30][31] hybrid composites, [32][33][34][35][36][37][38] graphene, 39,40 and nanowires (NWs) or nanotube assemblies [41][42][43][44] need to be integrated on various flexible substrates. 45 About a decade ago, flexible electronic skins (e-skins) for pressure sensing were first introduced with polymer-based switching matrices for future displays, robots, and prosthetics of mechanical communications [ Figure 1(a)].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, measurement of electrical conductivity under strain can be a probe to understanding microstructural changes. Carbon black-filled conductive rubbers have wide applications, such as pressure sensitive sensors which can be used for shock proof switches [7], sensors for measurement of vehicle weights to collect toll tax on roads [8], and smart flexible sensors adapted to textile structures, able to measure their strain deformations [9], and tactile sensor that is thin and flexible and able to attach to a curved surface and will make the robot operate in unstructured environments [10,11]. For an electronic application of the CPC, the sensor should have a good linear behavior (with the effect of elongation), while the specific electrical resistivity of the system should be in a measurable range (<100 Ω·m) [12].…”
Section: Introductionmentioning
confidence: 99%
“…For the first case, the elongation of the sensor in one direction will cause a shrinking in the other two directions resulting in a decrease in cross-section, and the electrical resistance will increase. In the second case, the intrinsic alteration of the sensor by an external phenomenon may be caused, for example, by a change in the electrical conduction of the conductive particles, or by a modification in the quality of the polymer/filler particle interface [15]. Note that, in our approach, we will limit ourselves to the case where the change in conductivity is mainly due to a geometric change in the resistance section.…”
mentioning
confidence: 99%
“…These sensors are used, in fact, for a specific application in the aeronautical field, which consists in measuring the fabric deformations in a parachute canopy manufacture. The study of these materials has shown that the variation of the electrical resistance of these CPC sensors can result from two phenomena [15]. The first one is related to a transformation in the sensor geometry.…”
mentioning
confidence: 99%